Cellular and humoral immune response after mRNA‐1273 SARS‐CoV‐2 vaccine in liver and heart transplant recipients. Issue 12 (4th August 2021) - Herrera, Sabina; Colmenero, Jordi; Pascal, Mariona; Escobedo, Miguel; Castel, María A.; Sole‐González, Eduard; Palou, Eduard; Egri, Natalia; Ruiz, Pablo; Mosquera, Mar; Moreno, Asunción; Juan, Manel; et al.
Abstract : Recently published studies have found an impaired immune response after SARS‐CoV‐2 vaccination in solid organ recipients. However, most of these studies have not assessed immune cellular responses in liver and heart transplant recipients. We prospectively studied heart and liver transplant recipients eligible for SARS‐CoV‐2 vaccination. Patients with past history of SARS‐CoV‐2 infection or SARS‐CoV‐2 detectable antibodies (IgM or IgG) were excluded. We assessed IgM/IgG antibodies and ELISpot against the S protein 4 weeks after receiving the second dose of the mRNA‐1273 (Moderna) vaccine. Side effects, troponin I, liver tests and anti‐HLA donor‐specific antibodies (DSA) were also assessed. A total of 58 liver and 46 heart recipients received two doses of mRNA‐1273 vaccine. Median time from transplantation to vaccination was 5.4 years (IQR 0.3–27). Sixty‐four percent of the patients developed SARS‐CoV‐2 IgM/IgG antibodies and 79% S‐ELISpot positivity. Ninety percent of recipients developed either humoral or cellular response (87% in heart recipients and 93% in liver recipients). Factors associated with vaccine unresponsiveness were hypogammaglobulinemia and vaccination during the first year after transplantation. Local and systemic side effects were mild or moderate, and none presented DSA or graft dysfunction after vaccination. Ninety percent of our patients did develop humoral or cellular responses to mRNA‐1273 vaccine. Factors associated with vaccine unresponsiveness were hypogammaglobulinemia and vaccination during the first year after transplantation, highlighting the need to further protect these patients. Abstract : The vast majority of heart and liver transplant patients develop humoral or cellular responses to mRNA‐1273 vaccine. See editorial by Danziger‐Isakov and Sester on page 3827 .